(untitled) - Lea, Homer (New York, 1909)
One of the foremost strategists of the American Army in the first decade of the twentieth century warns of the great danger of militarized Japan and forcasts -- 44 years before it actually happened -- the Japanese invasion of the Philippines.
Keywords: Eastern question (Far East),Câu hỏi về phương đông (Viễn Đông)